Malocclusion and the need for orthodontic treatment in 12-year-old adolescents (Research, Society and Development, 2021)
The treatment of malocclusions in a public health system requires the collection of data on the orthodontic needs of a given population. Thus, different recording methods have been developed to classify occlusion problems. The objective in this study was to investigate the prevalence of malocclusions and the normative need for orthodontic treatment in 12-year-olds. This is a cross-sectional epidemiological study carried out with 461 students from public schools. For the evaluation, clinical examinations were performed using the Angle’s Classification and the Dental Aesthetics Index (DAI). It was observed that 8.89% had normal occlusion, 56.83% Class I, 24.08% Class II and 10.20% Class III. None or need for mild orthodontic treatment was observed in 47.51%; elective treatment was present in 20.61%, highly desirable in 13.45% and mandatory in 18.44% of young people. Among the results of clinical examinations for the diagnosis of malocclusions using the Angle’s Classification, an association with the Dental Aesthetic Index (DAI) was observed (p